Quality of water from springs in the administrative region of Brazlândia, located in the Descoberto River micro hydrographic basin, Federal District, Brazil (Research, Society and Development, 2023)
Water is essential for life and used for multiple purposes such as human consumption, agriculture and recreation. In this way, it must present physical-chemical characteristics adequate to the quality standards, without risk to human health. This study aimed to verify the water quality of the springs, in the municipality of the Regional city of Brazlândia, DF, Brazil, in the year 2021. The research was carried out in May and the water samples were collected in eleven points of springs and from Córrego de Brazlândia, in Veredinhas Park, from each sampling point, three liters of water were collected randomly and separately, for the investigation of enteroparasites, using the spontaneous sedimentation method. For the analysis of thermotolerant coliforms and Escherichia coli, three samples (100 ml) were collected and analyzed using the Colilert method. The organoleptic characteristics, pH, and presence of solid residues were verified in addition to observing the existence of the gallery forest. All areas analyzed had the presence of solid residues and most of the collection points had water with a cloudy appearance, unpleasant odor, and pH 6. All samples were positive for thermotolerant coliforms and presented at least one evolutionary form of intestinal parasite. Water sources in Brazlândia, DF, Brazil, are contaminated with potentially pathogenic microorganisms for humans. Thus, measures must be taken to minimize this situation, in addition to guidance and work with the community, to help in the recovery of these sources.